Moderating effect of gross domestic production on the association between share ownership of CEO and strategic risk-taking of airlines - Joonho Moon (Global Business & Finance Review (GBFR), 2024)
Purpose: The purpose of this research is to examine the moderating effect of gross domestic product on the relation-ship between share ownership and strategic risk-taking of airlines. Theoretical foundation of this work is upper echelon theory and contingency theory. Design/methodology/approach: The sample of this work is publicly traded airlines in the US stock market: NASDAQ, AMEX, and NYSE. For data collection, this work employed Annual 10-K, Bureau of economic analysis, Compustat, and Execucomp using SIC code 4512. 15 airlines were used and the study period is 1999-2019. For testing the research hypotheses, this study implemented multiple linear regression analysis. Findings: The results indicated that gross domestic product positively moderates the relationship between share ownership of CEO and strategic risk-taking of airlines. Research limitations/implications: The practical implication of this work is for the information provision of share-holders and potential investors for airline stocks. Originality/value: This research is worthy by elucidating the moderating effect of gross domestic product regarding top managers' decision making domain.
Keywords: 650; Airline; Chief executive officer; Share ownership; Gross domestic product; and Strategic risk-taking